Biofilm formation is a risk factor for late and delayed complications of filler injection - Zhang, You-liang; Sun, Zhong-sheng; Hong, Wei-jin; Chen, Yin; Zhou, Yang-fan; Luo, Sheng-kang (Frontiers in Microbiology, 2024)
Introduction Biofilm formation is a major cause of delayed-graft complications. Similarly to implants, dermal fillers carry the risk of biofilm formation, which can lead to the development of nodules, chronic inflammatory reactions, abscesses and other complications. In this study, we investigated the late or delayed complications associated with biofilm formation on dermal fillers. Methods In this retrospective analysis, we analyzed all cases of complications caused by filler injections at a single center between January 2017 and December 2022, the majority of which comprised nodule formation and chronic persistent inflammatory reactions. The risk of biofilm formation with fillers was summarized and analyzed based on the results of bacterial culture and pathological examination. Results Sixty-one patients were enrolled, including 42 cases of nodule formation, 15 of chronic inflammatory reactions, and 4 of active infection. Bacterial culture of the tissue samples obtained from seven patients after surgical treatment were positive, and comprised four cases of Staphylococcus aureus, one case of Staphylococcus epidermidis, one case of Staphylococcus saprophyticus and one case of Mycobacterium abscessus. The corresponding histopathological results indicated extensive mononuclear lymphocyte infiltration, with a giant cell reaction in the fibrous connective tissue. Conclusion The results of this study suggest that biofilm formation is a significant risk factor for late and delayed complications following filler injection, and is caused by the contamination of resident bacteria and recessive infection at the injection site.